Enhancing Mathematical Achievement through the Think-Pair-Share Cooperative Learning Model with Higher-Order Thinking Skills Questions - Zaki, Ahmad; Sahid, Sahid; Nurhaliza, Ratih; Naufal, Muhammad Ammar; Huda, Miftachul; Hassan, Muhammad Nasiru (Jurnal Riset Pendidikan Matematika, 2024)
This study examines the influence of the Think-Pair-Share (TPS) model with Higher-Order Thinking Skills (HOTS) questions, on students' achievement. The experimental research was conducted at Junior High School of 1 Ampana Tete and featured 56 Grade IX students. These students were divided into an experimental group that received TPS with HOTS and a control group that received conventional. Descriptive and inferential statistics were utilized to analyze pretest and posttest scores. The results indicated that the experimental group showed a noteworthy enhancement in their achievements, as seen by an average posttest score of 59.07, which was significantly higher than the control group's score of 40.86. The experimental group achieved a normalized gain (N-Gain) of 0.517, indicating a medium level of improvement. In contrast, the control group's N-Gain was 0.303, indicating a low level of improvement. The results of t-test have indicated that the TPS model combined with HOTS questions, has a considerable favorable impact on students' performance. This study provides evidence for the efficacy of cooperative learning practices in improving academic performance in the field of mathematics. The findings indicate that instructors should integrate TPS and HOTS questions to cultivate a more engaging and intellectually stimulating learning atmosphere.